(Trans)languaging-for-learning: A perspective from the South - Carolyn McKinney; Robyn Tyler (Reading & Writing)
Background: While the concept of translanguaging has gained significant traction in education in multilingual contexts, it is also debated and contested. Claims are made about what translanguaging can and cannot do, how different it might be from code-switching, whether it arises from a single repertoire of language resources or from use of separate languages, and whether it is detrimental to or supportive of the development and inclusion of marginalised languages.